Engineering novel nanomaterials for energy storage: NiO/CuO/α-Fe2O3 nanocomposites synthesized via hydrothermal method - Upadhyay L.; Dhanapandian S.; Suthakaran S.; Yadav B.; Kar K.K.; Kumar D.; Sundaramurthy S. (My University, 2025)
NiO/CuO/α-Fe2O3 ternary nanocomposites (TNCs) were synthesized via a hydrothermal method using a molar ratio of Ni: Cu: Fe = 5:3:1 for supercapacitor applications. The produced TNCs were analyzed through multiple analytical methods. XRD confirmed the crystalline phases of NiO, CuO, and α-Fe2O3 with a mean crystallite size of 33.31 nm. The FESEM revealed a uniform cubic-shaped structure with a mean particle size of 54 nm while EDAX confirmed the elemental composition. UV–Vis DRS showed a bandgap of 1.73 eV, highlighting the material's potential for electrochemical performance. XPS analysis provided insights into the chemical valance states of Ni, Cu, and Fe while BET analysis showed a moderate specific surface area of 12.59 m2/g and mesoporous characteristics of the TNCs. The VSM analysis revealed a strong ferromagnetic behavior of the prepared TNCs. Electrochemical evaluations demonstrated a specific capacitance of 911 F g−1 at 5 mV s−1 (CV) and 894 F g−1 at 0.5 A g−1 (GCD). EIS revealed low equivalent series resistance and good capacitance retention across frequencies. These results underscore the potential of NiO/CuO/α-Fe2O3 TNCs for efficient charge storage in supercapacitor applications. © 2024 Elsevier B.V.